Original paperAccess-site complications of percutaneous diagnostic and therapeutic procedures in coronary artery disease: pseudoaneurysms and arteriovenous fistulas - Karalus, Dariusz; D. Kasprzak, Jarosław; Szymczyk, Ewa; Peruga, Jan Z.; Michalski, Błażej; Lipiec, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background: Pseudoaneurysms (PAs) and arteriovenous fistulas (AVFs) are among the most serious access-site vascular complications of percutaneous diagnostic and therapeutic procedures in coronary artery disease. Aim: To assess the clinical course and methods of treatment of these access-site complications. Material and methods : Medical records of 26 949 patients who underwent coronary angiography and/or angioplasty in the period 2000-2009 in two tertiary referral level catheterization laboratories were reviewed. We identified 91 patients with confirmed access-site complications: 90 iatrogenic PAs and 3 AVFs (2 of which were accompanied by PA). Results: Prolonged compression with an elastic bandage was the most frequently (55 patients) used first-line treatment of PAs. Others included compression with ultrasound probe (15 patients), ultrasound-guided thrombin injection (11 patients), and surgery (3 patients). Forty-seven patients with PAs required second-line treatment, which in most cases was thrombin injection (23 patients). Thrombin injection and compression with ultrasound probe were the most frequently used third-line treatment techniques. The overall effectiveness (complete closure of PA) of the treatment techniques was: surgery – 100%, thrombin injection – 86.8%, compression with ultrasound probe – 70.8%, prolonged compression with elastic bandage – 42.4%, observation – 0%. Conclusions: Significant access-site complications of percutaneous coronary interventions, especially AVFs, are infrequent. Spontaneous closure of the PA during hospitalization was not observed. Both thrombin injection and compression with an ultrasound probe allow for fast and effective treatment of iatrogenic PA. However, surgery remains the most effective treatment technique. Prolonged compression with an elastic bandage offers low efficacy.